MODEL BLENDED LEARNING BERBASIS WORDWALL MENINGKATKAN KEMAMPUAN LITERASI MATEMATIS DAN SELF-EFFICACY - Ramadhani Ramadhani; Suci Fitriani Nasution (JURNAL MATHEMATIC PAEDAGOGIC, 2023)
The assessment that is currently being developed in the world of education is (KLM) or mathematical literacy ability and is measured from (SE) or self-efficacy of students. This study aims to determine whether students' abilities can increase with the model that has been implemented. The researcher used a quasi-experimental design with a "pretest-posttest control group design". All members were used as a population of 84 students from SMA Angkasa 1 Lanud Soewondo Medan with 56 tenth grade students as samples. two Classes were divided into 2 groups, namely experimental and control. The instruments or measuring instruments used are description tests and questionnaires. Samples are taken at random. From the overall results obtained by students in the experimental class in mathematical literacy skills, it was obtained 32% of students who reached a high level, 65% medium levels and 3% achieved low levels. While the results in the control class were 3% of students who achieved high levels, 40% of sedans and 57% of students who achieved low levels. In addition, because learning is accompanied by wordwall applications (learning games), students find learning more enjoyable and eager to repeat it.Keywords: Mathematical Literacy Skills, Self-Efficacy, Blended Learning, Wordwall